Does Trust Matter for Entrepreneurship: Evidence from A Cross-Section of Countries - Oasis Kodila-Tedika; Julius A. Agbor (African Governance and Development Institute (AGDI), 2015)
Differences in trust levels between countries explain the observed discrepancies in entrepreneurial spirit amongst them. We test this hypothesis with a cross-section of 60 countries in 2010. Our findings suggest that about half of the variation in entrepreneurial spirit across countries in the world is driven by trust considerations. This result is robust to regional clustering, to outliers and to alternative conditioning variables. The findings of the study suggest that while formal incentives to nurture entrepreneurship must be maintained, policy-makers should also seek to pay attention to the role of trust cultivated through informal networks.
Keywords: 330; trust; institution; entrepreneurship